Factors associated with operating-room extubation after emergency craniotomy - Saringcarinkul A. (2017)
© 2016, Medical Association of Thailand. All rights reserved. Objective: To determine clinical factors and outcomes associated with operating-room extubation. Material and Method: Three hundred seventy three medical records of emergency craniotomy were reviewed. The author categorized by whether the patients underwent operating-room extubation (ORE) or not (nORE). Demographic and perioperative factors were reviewed for association with ORE, e.g. Glasgow coma scale score (GCS), brain edema, and duration of anesthesia. Outcomes included clinical status, and duration in intensive care unit and hospital stay. Results: Of the 373 patients, 130 (35%) had been extubated in the operating room. The strongest factors associated with ORE were no perioperative brain edema (adjusted odds ratio [OR] = 76.44 [95% confidence interval 9.46-617.50] , p < 0.001), high GCS score from 13 to 15 (adjusted OR = 3.74 [1.99-7.01], p < 0.001), and better ASA physical class IE or IIE (adjusted OR = 2.09 [1.21-3.59], p = 0.008). The median lengths of time in the intensive care unit (ICU) were significantly shorter among OREs (3 days, range 2-5) than nOREs (4 days, range 3-8), p < 0.001, as well as for duration of hospital stay (7 days, range 4-10 vs. 8 days, range 5-13, respectively, p = 0.008). Conclusion: After emergency neurosurgery, ORE is associated with absent cerebral edema, high GCS score, and better ASA status.